Properties of microcrystalline cellulose prepared from oil palm empty fruit bunch at different sulfuric acid concentration and hydrolysis temperature - J., Sukaimi; W. N. H., Wan Abdullah; Muhammad Arif Fahmi, Supian; Saidatul Shima, Jamari; Nurul Aini, Mohd Azman; S., Mohamad; Mohd Faizal, Ali (IOP Publishing, 2019)
In this study, a green process was studied for the preparation of microcrystalline cellulose (MCC) from empty fruit bunch (EFB) by two steps of processes: steam explosion treatment and hydrolysis of sulphuric acid (H2SO4). Prior to hydrolysis, the EFB was treated with steam at 17 bar for 10 min. The effects of hydrolysis condition for example H2SO4 concentration were analyzed according to morphology, purities and also percentage of crystal and compared with the commercially available MCC. The higher crystallinity index was observed as the cellulose hydrolyzed with 3.5 M of H2SO4. The yield of MCC prepared was high as by using this condition. However, morphological images by SEM showed insignificant improvement as the synthesized MCC is still in fibres strand and looks like rod-shaped. This result might due to poor treatment process during the steam explosion treatment. The result was confirmed by the FTIR analysis which provided clear evidence that the characteristic peaks of lignin and hemicellulose were present in the spectrum. It can be concluded that the MCC can be produced with the hydrolysis process of 3.5 M and 80 °C.